The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/1526602820937432
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Aneurysm Sac Shrinkage After Endovascular Aneurysm Repair

Abstract: Purpose: To investigate whether patients who develop aneurysm sac shrinkage following endovascular aneurysm repair (EVAR) have better outcomes than patients with a stable or increased aneurysm sac. Materials and Methods: The Healthcare Databases Advanced Search interface developed by the National Institute for Health and Care Excellence was used to interrogate MEDLINE and EMBASE. Thesaurus headings were adapted accordingly. Case-control studies were identified comparing outcomes in patients demonstrating aneur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 25 publications
2
17
0
Order By: Relevance
“…This research showed a significantly lower all-cause mortality in patients with a shrinking AAA one-year after EVAR, compared to patients with a stable AAA, confirming data of previous studies [ 7 , 8 , 9 ]. In addition, one death of a patient with a stable AAA was EVAR-related, while none of the patients with AAA shrinkage died from this cause.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This research showed a significantly lower all-cause mortality in patients with a shrinking AAA one-year after EVAR, compared to patients with a stable AAA, confirming data of previous studies [ 7 , 8 , 9 ]. In addition, one death of a patient with a stable AAA was EVAR-related, while none of the patients with AAA shrinkage died from this cause.…”
Section: Discussionsupporting
confidence: 90%
“…A stable or shrinking aneurysm diameter after EVAR has traditionally been considered a treatment success. However, recent studies indicate that patients with AAA shrinkage, at one-year after EVAR, have significantly better long-term outcomes compared to patients with growing AAA, but also to those with stable AAA [ 7 , 8 , 9 , 10 , 11 ]. These outcomes include fewer reinterventions and late complications, less rupture, and a lower all-cause mortality [ 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We were interested to note this article by Antoniou et al 1 focusing on aneurysm sac shrinkage as a prognosticator for positive outcomes after endovascular aneurysm repair (EVAR), particularly in terms of reduction of rates of reintervention, late aneurysm rupture, other late complications—all considered to be the drawbacks of EVAR—and even death. This would suggest a need to look for particular adjuncts/interventions that might increase the incidence of post-EVAR sac shrinkage, and this aspect has not really been touched upon.…”
mentioning
confidence: 99%
“…We propose a surveillance algorithm that takes account of recommendations from the 2 major vascular society clinical practice guidelines 2,3 and considers the most contemporary evidence, applying a color code, that is, red requiring intervention, yellow requiring further investigations or more intensive surveillance, and green raising no concerns (Figure 2). 4 In this algorithm, after the 30-day computed tomography (CT) scan, we propose different paths based on the CT scan findings indicated by the color code, that is, ultrasound (US) surveillance (± abdominal X-ray) at 12 months if there is no endoleak or there is only a type II endoleak, further investigations with contrast-enhanced US or digital subtraction angiography (and subsequent treatment if necessary) if there is an indeterminate endoleak, or immediate treatment if the CT scan shows a type I or III endoleak. Following the 12-month US scan and in the absence of a malignant or indeterminate endoleak, the mode and frequency of surveillance is determined by the sac behavior and the presence of type II endoleak as follows: The proposed algorithm adopts a pragmatic approach to different modes and imaging frequencies.…”
mentioning
confidence: 99%